MISTIK KEJAWEN DI HOTEL NATOUR GARUDA - Suwardi Suwardi (Jurnal Penelitian Humaniora, 2002)
Abstact Javanese mystical ritual in Natour Garuda hotel is spiritual application for approaching upon God. The ritual held every Eve Tuesday Kliwon has been running since 20 May 1997 up to now. This research aims to give the understanding ethnographic analytic to word the Javanese mystical ritual existence which during this modern still done by part of Javanese community. Taking participant observation and in depth interview to the informant snowballingly held the data collection. The research result describes the Javanese mystical ritual in Natour Garuda  hotel is considered unique, because it is gatheredly done, in the relatively busy place, and it has been packed into the spiritual art collaboration. The ritual procession is set in accordance with structure of the leather puppet show consisting of seven phases. The seven phases inviting performance arts aspects towards the process manunggaling kawulo Gusti. Concurring with this, either the mystic or the hotel management will get the material value is the invisible essence spiritually. As seen from the aspect of function, the material value is more supporting the hotel vision, i.e, the direction into the traditional culture development, values, and Javanese mystical ritual meaning for the supporters. Keywords: Javanese mystical ritual, hotel Natour Garuda, cultural tourism